Plan de desarrollo local participativo de la comunidad de Cuicuno de la parroquia Guaytacama del cantón Latacunga, provincia de Cotopaxi. - Ángeles Noemí, Tapia Trujillo (2011)
The struggle to eradicate poverty and economic and social inequalities in both the rural, marginal urban and urban sectors has been incessant. The initiatives, programs, projects for this objective have not been allowed to wait, so much so that international organizations such as the UN raised as Millennium Goal N.1, Reduce poverty by half, between 1990 and 2015 worldwide. In our country we have the National Development Plan 2007-2010 and the National Plan 2009-2013 with the content of the 12 National Objectives for Good Living. Most of the decentralized autonomous governments in the development plans, their vision is to improve the quality of life of the inhabitants. With this brief analysis we deduce that the development plans have become a useful tool that becomes an effective guide for the work of local governments, with mechanisms for participation, control, monitoring, and citizen oversight. A new way of conceiving development is based on the use of potential, own resources and the person as human capital and generator of growth.